RAZVOJ TJELESNIH SPOSOBNOSTI MLADIH FUDBALERA MEDITERANSKE REGIJE U CRNOJ GORI UTICAJEM SPORTSKOG TRENINGA ( - Duško Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
This extensive research, which includes fifteen- year -old male gander examinees, is representive specimen of this level in Montenegro. Examinees are divided according to their age, geographv location (coastal area) and activitv in football training. Group is divided into two sub-groups, examinees who are training football and in the other, those who are not training football. The final definition of the sub-groups would be: First sub-group: fifteen-year-old boys who are training football. Second sub-group: fifteen-year-old boys who are not training football. Variables used in this research have inclusiveb/ motor function characteristics. This research examines differences of motor function values betvveen the subgroups and individuals according to above-mentioned variables. Aim of research According to preliminary research it was possible to identify a task of actual research, which is identification of eventual differences in general motor function abilities between fifteen-year-old boys from coastal area who are included actively in process of sport training, and those, from the same area, vvho are not included actively in systematic training. Prof. dr